Gastropod first intermediate hosts for two species of Monorchiidae Odhner, 1911 (Trematoda): I can't believe it's not bivalves!. Issue 12 (November 2021) - Wee, Nicholas Q-X.; Cribb, Thomas H.; Corner, Richard D.; Ward, Selina; Cutmore, Scott C.
Graphical abstract: Highlights: Sporocysts and cercariae corresponding morphologically to those of monorchiids are reported from vermetid gastropods. These are the first monorchiid intramolluscan stages from gastropods and represent a striking intermediate host shift. All other known monorchiid life cycles use a bivalve first intermediate host. The infections are genetically matched to two species of Hurleytrematoides, H. loi and H. morandi. The exceptional feeding biology of vermetids might be key in their adoption of some trematode groups. Abstract: The trematode superfamily Monorchioidea comprises three families of teleost parasites: the Monorchiidae Odhner, 1911, Lissorchiidae Magath, 1917, and Deropristidae Cable & Hunninen, 1942. All presently known lissorchiid and deropristid life cycles have gastropods as first intermediate hosts, whereas those of monorchiids involve bivalves. Here, we report an unexpected intermediate host for monorchiids; two species of Hurleytrematoides Yamaguti, 1954 use gastropods as first intermediate hosts. Sporocysts and cercariae were found infecting two species of the family Vermetidae, highly specialised sessile gastropods that form calcareous tubes, from two locations off the coast of Queensland, Australia. These intramolluscan infections broadly corresponded morphologically to those of known monorchiids in that the cercariae have a spinous tegument, oral and ventral suckers, a simple tail and distinct eye-spots. Given the simplified morphology of intramolluscan infections, genetic data provided a definitive identification. ITS2 rDNA and cox 1 mtDNA sequence data from the gastropod infections were identical to two species of Hurleytrematoides, parasites of butterflyfishes (Chaetodontidae); Hurleytrematoides loi McNamara & Cribb, 2011 from Moreton Bay (south-eastern Queensland) and Heron Island (southern Great Barrier Reef) and Hurleytrematoides morandi McNamara & Cribb, 2011 from Heron Island. Notably, species of Hurleytrematoides are positioned relatively basal in the phylogeny of the Monorchiidae and are a sister lineage to that of species known to infect bivalves. Thus, the most parsimonious evolutionary hypothesis to explain infection of gastropods by these monorchiids is that basal monorchiids (in our analyses, species of Cableia Sogandares-Bernal, 1959, Helicometroides Yamaguti, 1934 and Hurleytrematoides ) will all prove to infect gastropods, suggesting a single host switching event into bivalves for more derived monorchiids (17 other genera in our phylogenetic analyses). A less parsimonious hypothesis is that the infection of vermetids will prove to be restricted to species of Hurleytrematoides, as an isolated secondary recolonisation of gastropods from a bivalve-infecting lineage. Regardless of how their use arose, vermetids represent a dramatic host jump relative to the rest of the Monorchiidae, one potentially enabled by their specialised feeding biology.